UV-induced dissociation of CH2BrI probed by intense femtosecond XUV pulses. (5th January 2022) - Köckert, Hansjochen; Lee, Jason W L; Allum, Felix; Amini, Kasra; Bari, Sadia; Bomme, Cédric; Brauße, Felix; Brouard, Mark; Burt, Michael; Cunha de Miranda, Barbara; Düsterer, Stefan; Eng-Johnsson, Per; et al.
Abstract: The ultraviolet (UV)-induced dissociation and photofragmentation of gas-phase CH2 BrI molecules induced by intense femtosecond extreme ultraviolet (XUV) pulses at three different photon energies are studied by multi-mass ion imaging. Using a UV-pump–XUV-probe scheme, charge transfer between highly charged iodine ions and neutral CH2 Br radicals produced by C–I bond cleavage is investigated. In earlier charge-transfer studies, the center of mass of the molecules was located along the axis of the bond cleaved by the pump pulse. In the present case of CH2 BrI, this is not the case, thus inducing a rotation of the fragment. We discuss the influence of the rotation on the charge transfer process using a classical over-the-barrier model. Our modeling suggests that, despite the fact that the dissociation is slower due to the rotational excitation, the critical interatomic distance for charge transfer is reached faster. Furthermore, we suggest that charge transfer during molecular fragmentation may be modulated in a complex way.